1998
DOI: 10.2466/pr0.1998.83.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review of Biorhythm Theory

Abstract: Biorhythm theory which became popular with the general public in the late 1960s held that three different biorhythm cycles influenced three different general aspects of human behavior. There was a 23-day cycle which influenced physical aspects of behavior. A 28-day cycle influenced emotions and a 33-day cycle influenced intellectual functions. Further, according to the theory, these three cycles started at birth and progressed, sinusoidally, throughout life varying not a bit with environmental or physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The idea of different biorhythm cycles that influence human behaviour can be traced back to the German surgeon Wilhelm Fliess in the 1890s, who proposed a 23-day male period and a 28-day female period (Hines, 1998). More recent studies identified three different biorhythm cycles: a 23-day cycle influences physical aspects such as energy, resistance to disease, endurance; a 28-day cycle influences emotions such as sadness, elation, moodiness, creativity and a 33-day cycle influences intellectual functions such as alertness, memory and reasoning ability (Thommen, 1968).…”
Section: Photoperiod Mood and Risk Aversionmentioning
confidence: 99%
“…The idea of different biorhythm cycles that influence human behaviour can be traced back to the German surgeon Wilhelm Fliess in the 1890s, who proposed a 23-day male period and a 28-day female period (Hines, 1998). More recent studies identified three different biorhythm cycles: a 23-day cycle influences physical aspects such as energy, resistance to disease, endurance; a 28-day cycle influences emotions such as sadness, elation, moodiness, creativity and a 33-day cycle influences intellectual functions such as alertness, memory and reasoning ability (Thommen, 1968).…”
Section: Photoperiod Mood and Risk Aversionmentioning
confidence: 99%
“…The study describes the characteristics of the main biorhythms [16,17]. Rhythms are classified according to the length of the period.…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…The results of the study of circadian rhythms are presented in various studies [18][19][20][21]. There are also biorhythms with periods: 7-14 days; 21-43 days; about a year; about a few years [16,17].…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…The positive phase brings optimism, joy, openness, tolerance, and self control. During the low end of the cycle (day 16 to day 28) your emotions are in a recuperative state, as explained by Hines (1998). You are more inclined to be irritable and negative.…”
Section: (B) the Emotional Biorhythmic Cycle (28 Days)mentioning
confidence: 99%
“…Biorhythm cycles are composed of positive phase, negative phase and nodal points where the curve crosses the abscissa. According to Hines (1998) each cycle starts on the first positive phase at the moment of birth, the positive phases correspond to periods of better performance, and the negative phases correspond to periods of poor performance and greatest susceptibility. Critical periods are usually of 24 h/48 h duration.…”
Section: Introductionmentioning
confidence: 99%